The Meaning of Justice in the Qur'an and the Implications of Islamic Law on Polygamy Permits: Harmonization of Islamic Law and Positive Law with the Maqasidi Tafsir Approach - Daud, Ilyas (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This research aims to explain the meaning of justice in QS. An-Nisa: 3 through the paradigm of maqasidi interpretation (tafsir maqasidi) and its implications in Islamic law regarding the permission for polygamy. Tafsir maqasidi is a type of exegesis that examines the meanings of the words in the Noble Qur'an and their broader linguistic implications, along with the wisdom and objectives behind the revelation of the Qur'an and the legislation of Islamic laws. These objectives encompass universal values, namely maqasid al-shari'ah (the higher purposes of Islamic law) and maqasid al-Qur'an (the objectives of the Qur'an). This study employs a qualitative method with a tafsir maqasidi approach, involving textual analysis of the verse, historical context, and integration with the principles of maqasid al-shari'ah and empirical evidence related to the impacts of polygamy. The issues this paper seeks to address are: first, the absence of a definitive Islamic legal ruling on whether polygamy without the wife's permission is permissible or not. Second, the lack of alignment between Islamic legal rulings on polygamy permission and the provisions of Law No. 1 of 1974 of the Republic of Indonesia and the Compilation of Islamic Law, which stipulate that the wife's consent is mandatory. The findings indicate that the meaning of justice in QS. An-Nisa: 3, when understood through the lens of tafsir maqasidi, aims to protect women's well-being physically, mentally, and emotionally. Thus, polygamy without consent constitutes an act that contradicts the principle of justice and undermines maqasid al-shari'ah in safeguarding women's dignity and rights. Therefore, from the perspective of interpreting QS. An-Nisa: 3, obtaining permission for polygamy becomes an obligatory requirement.